Buket Uang Dalam Perspektif Hukum Islam Dan Hukum Positif - Kisanda Midisen (ITB AAS INDONESIA Surakarta, 2023)
This article aims to determine the perspective of Islamic law and positive law in Indonesia on the phenomenon of the rampant sale and purchase of a bouquet of money in the form of a bouquet of flowers. And at the same time trying to compare the legal point of view in Islamic law and positive law on the bouquet of money. This research is a field and literature research, with the type of qualitative observative and descriptive analytical research whose explanation uses exposure and description of the problem being studied. Data collection techniques are carried out by conducting field observations of existing phenomena and then clashing with the point of view of Islamic law and positive law. The data analysis technique used is by performing the stages of data collection, data reduction, data presentation, and drawing conclusions from the research results. The results of the study are based on the perspective of Islamic law that the use of money as a bouquet is allowed if there are no transactions that contain elements of usury, while in positive law what must be considered is that it does not change the value and function of money and does not conflict with Law Number 7 Article 25 of 2011 concerning Currency.